IMPLEMENTASI LESSON STUDY UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PADA MATAKULIAH KALKULUS MULTIVARIABEL - Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Through improving the quality of learning, it is expected that the quality of the graduate will also increase. One approach to improve the quality of learning iswith lesson study activities. Lesson study is one of the approaches to improvethe process and learning outcomes that are implemented in a collaborative andsustainable way. The implementation of this lesson study used learning model ofProject based learning (PjBL) with an inquiry approach accompanied bystudent worksheet. This research used a qualitative approach with thedescriptive analysis method. There are three stages of lesson study activities;plan, do, and see. The subject of the study was students of mathematicseducation program of FMIPA UNIMUS on Multivariable Calculus course inacademic year 2017/2018. The application of lesson study to the MultivariableCalculus course was thoroughly well-conducted. Through lesson study, thequality of learning is increasing. This can be seen in terms of planning,implementation and evaluation. Further reflection on the drawing graphmaterial in R3 was separated between linear equations and quadraticequations. The overall application of lesson study in multivariable calculuscourses runs well and can be applied to other subjects.Keywords: Inquiry, Lesson Study, Multivariable Calculus, Project based learning